Innovation and Performance in Malaysia’s Manufacturing Companies: The Control Variable of the Company’s Year of Establishment - Loong, Ang Hong; Laison Sondoh Jr, Stephen; Kim Huat, Lee (Malaysian Journal of Business and Economics (MJBE), 2019)
This study was conducted an exploratory study to investigate the extent to which the company’s year of establishment affects innovation and performance in Malaysia’s manufacturing companies. The findings revealed that the study supports positive relationship between innovation and innovative performance with the influence of the company’s year of establishment is as consistent as claimed in the previous studies. There are four most ranked categories of innovation based on the product, process, marketing and organization examined in the study. However, results found that marketing and organizational innovation did not have significant relationship with innovative performance due to low level of customer service and the emphasizing only on purely production by Malaysia’s manufacturing companies. This study applied quantitative approach through a self−administrated questionnaire and believed to be able to contribute to the importance of each category of innovation efforts as a fundamental source of competitive advantage that is a necessary precondition to boost a company’s ability to penetrate the market. A total of 323 samples were collected and analysed using Partial Least Squares structural equation modelling technique. Thus, this study can reflect its current performance and represent the true position of manufacturing companies in Malaysia.